An Updated Meta-Analysis Comparing Artificial Cervical Disc Arthroplasty (CDA) Versus Anterior Cervical Discectomy and Fusion (ACDF) for the Treatment of Cervical Degenerative Disc Disease (CDDD). Issue 23 (December 2015) - Gao, Fuqiang; Mao, Tianli; Sun, Wei; Guo, Wanshou; Wang, Yunting; Li, Zirong; Abhinav, Pradhan
Abstract : Study Design: A meta-analysis of published randomized controlled Trials (RCTs). Objective: The aim of this study was to compare the efficacy and safety of cervical disc arthroplasty (CDA) with anterior cervical discectomy and fusion (ACDF) for the treatment of one-level cervical degenerative disc disease (CDDD). Summary of Background Data: ACDF has been widely performed for the treatment of CDDD. However, the loss of motion at the operated level has been hypothesized to accelerated adjacent-level disc degeneration. CDA is designed to avoid the side effect of fusion. However, it is still uncertain whether CDA is more effective and safer than ACDF. Methods: We performed a meta-analysis of published RCTs to examine whether there was a superior clinical effects of CDA than ACDF. A PubMed database search through October 2014 was performed for relevant studies. We included RCTs that reported relevant data in the treatment of one-level CDDD, which were suitable for detailed extraction of data. Results: We identified 18 RCTs eligible for analysis. The results of the meta-analysis indicated longer operative times, more blood loss, lower neck and arm pain scores reported on a visual analog scale (VAS), better neurological success, greater motion at the operated level, fewer secondary surgical procedures in the CDA group than in the ACDF group ( P  < 0.05). The 2 groups had similar lengths of hospital stay, Neck Disability Index scores, and rates of adverse events ( P  > 0.05). Conclusions: Findings of the present meta-analysis indicated that CDA was an effective and safe surgical procedure for the treatment of one-level CDDD, and CDA was found to be more superior than ACDF in terms of VAS neck and arm pain, neurological success, range of motion at the operated level, and secondary surgical procedures. Level of Evidence: 1